The development of a public library data collection and analysis platform and its uses: a case study of the National Library Big Data Platform in Korea - Jungyeoun Lee,; Kwon, Nahyun (Malaysian Journal of Library and Information Science, 2023)
Public libraries reflect the contemporary way of life. In the era of the digital data age, actions carried out through libraries can be traced and analyzed to monitor the demand for library services. This study presents the development and utilization of Korea's National Library Big Data Platform (NLBDP), which was constructed to collect operational data from public libraries in the country and to build national open data platform for the participating libraries and for public use. This study analyzed 17 application cases that utilized NLBDP in order to understand the way the platform has been used. The findings showed that the types of data analyzed so far have been somewhat limited. It suggests needs for further enhancing the data quality and for diversifying data sources, such as individual local library operational data, surveys, demographics, news, and social media. The results also revealed that NLBDP has been utilized for seven distinct purposes: library operations and strategic planning; social trend analysis; collection management; redesigning library space; recruiting new patrons; library marketing; and non-library applications. Building an infrastructure for networked data analysis not only enables evidence-based decision-making in public libraries, but also extracts timely topics that can be developed as useful services for their community. The findings of this study highlighted the necessity to formulate national library data policies and gather data capable of measuring the social impact of libraries.